Analisis Kemampuan Pemahaman Konsep Matematis Materi Sistem Persamaan Linear Dua Variabel Ditinjau Dari Kemandirian Belajar Siswa Kelas VIII SMP Negeri 21 Mataram Tahun Ajaran 2021/2022 - Esti Winda Sari; Nyoman Sridana; Laila Hayati; Nurul Hikmah (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to describe the ability to understand mathematical concepts in the material of a two-variable linear equation system based on the learning independence of eighth grade students of SMP Negeri 21 Mataram in the 2021/2022 academic year. The type of research used is descriptive research.sampling technique used purposive sampling and the subjects used in this study were 6 students of class VIIIB SMP Negeri 21 Mataram which consisted of 2 students with high learning independence, 2 students with moderate learning independence, and 2 students with low independence. The selection of subjects in this study was based on using a learning independence questionnaire instrument. The data collection techniques using tests, questionnaires and interviews. The data analysis technique was carried out using the data reduction stage, the data presentation stage, and the conclusion drawing stage. The results obtained in this study are students with high learning independence are only able to fulfill 2 indicators of concept understanding, namely restating a concept that has been studied and presenting the concept in various forms of representation. Students with moderate independence are able to fulfill 3 indicators of concept understanding ability, namely providing examples and not examples of concepts that have been studied, restating a concept that has been studied and presenting concepts in various forms of representation. Then for students with low independence, they are only able to fulfill 2 indicators of concept understanding ability, namely providing examples and not examples of concepts that have been studied and restating the concepts that have been studied.